Smart Textile‐Based Personal Thermal Comfort Systems: Current Status and Potential Solutions. Issue 5 (17th March 2020) - Tabor, Jordan; Chatterjee, Kony; Ghosh, Tushar K.
Abstract: Thermophysiological comfort in humans is sought universally but seldom achieved due to biological and physiological variances. Most people in developed parts of the world rely on highly energy‐intensive, and inefficient central heating/cooling systems to achieve thermophysiological comfort which is rarely satisfactory. A potential solution to this issue is a wearable personal thermal comfort system (PTCS) consisting of textile‐based temperature and moisture sensors, thermal and moisture responsive actuators, and/or heating/cooling devices, that can sense the environment and physiology of the wearer, and accordingly provide an individualized thermal environment. Moving thermal regulation away from the built environment to the microclimate surrounding the human body using textiles has the potential to provide personalized thermal comfort and energy savings. Such a system may employ thermal comfort models and leverage the Internet of Things (IoT) and machine learning (ML) to understand individuals' comfort requirements. Herein, the current state of textile‐based active and passive comfort systems/technologies are summarized, including their environmental impact, major thermal comfort models, and factors influencing comfort. Also, active and passive textile‐based devices (sensors, actuators, and flexible heating/cooling devices) that may be incorporated into a textile‐based wearable PTCS are comprehensively discussed with an emphasis on their advantages, limitations, and prospects. Abstract : Factors influencing thermophysiological comfort and the role of textiles are reviewed. Traditional implementations as well as recent advances in textile‐based thermoregulation are explored, classified on the basis of passive and active systems. The role of sensors to drive autonomous thermoregulation via textiles is explored, with a focus toward the future of clothing‐based thermoregulation without the need for user intervention.